Ishin denshin an intercultural music experience with Japanese folk songs - Feria, Andre Lorenz B.; Valenciano, December (Diliman, Quezon City U.P. College of Music, 2019)
"This research/project aims to explore the use of Japanese folk songs arranged into choral works as materials for intercultural music education in the current Philippine education setting and choral music scene. Amidst the extensive development for the internationalization and globalization in our education system and the global music scene, the cultural and social implications of these efforts on our students have profoundly influenced the development of their cultural identity. Thus, the importance for a stronger, more inclusive intercultural music education. As such, three different choral groups of varying age groups were chosen as the main participants of the research: The UP Cherubim and Seraphim which represents the elementary level; the Quirino High School Choir which represents the secondary level; and the Junior Music Educators' Guild (JMEG) Chorale which represents the tertiary level".
Thesis (B. M. Music Education) -- University of the Philippines, Diliman.
Keywords: Folk songs, Japanese